Correlation between ApoE gene polymorphisms and the occurrence of urolithiasis - QIAN, BIAO (D.A. Spandidos, 2015)
The aim of the present study was to investigate the correlation between apolipoprotein E (ApoE) gene polymorphisms and the occurrence of urolithiasis and dyslipidemia. A total of 180 Uyghur individuals, including 90 urolithiasis patients and 90 healthy controls, were enrolled in this study. The blood lipid profiles of the patients and controls were investigated and compared, and the composition of the urinary calculi was determined. The polymorphisms of the ApoE alleles were analyzed using polymerase chain reaction-restriction fragment length polymorphism analysis. Three common genotypes of the ApoE gene, E3/3, E3/4 and E4/4, were detected in the urolithiasis patients and control group. In the patient group, 28 patients with the E3/3 genotype (30.1%), 58 patients with the E3/4 genotype (64.4%) and four patients with the E4/4 genotype (4.5%) were identified. By contrast, in the control group, 52 patients with the E3/3 genotype (57.8%), 35 patients with the E3/4 genotype (38.9%) and three patients with the E4/4 genotype (3.3%) were identified. The frequency of the E3/4 genotype was found to be significantly higher in the patient group when compared with the control group (χ2=12.96; P<0.001). In addition, the frequency of the E4 allele was significantly higher in the patient group when compared with the control group (χ2= 6.61; P=0.025). In conclusion, the occurrence of urolithiasis was found to be associated with ApoE gene polymorphisms, and the E4 allele may be a potential susceptibility factor for urolithiasis.